Polls and politics : the dilemmas of democracy - Genovese, Michael A.; Streb, Matthew J. (Matthew Justin), 1974- (State University of New York Press, 2004)
This hard-hitting and engaging examination of polls and American politics asks an essential question: do polls contribute to the vitality of our democracy or are they undermining the health of our political system? leading scholars address several key issues such as how various types of polls affect democracy, the meaning attributed to polling data by citizens and the media, the use of polls by presidents, and ow political elites respond--or do not respond--to public polls. the contributors assert that while polls treat z fine line between informing and manipulating the public, they remain valuable so long as a robust democracy obliges its political leaders to respond to the expressed will of the people.